Investigating the potentials of phage therapy in burkholderia pseudomallei infection / Ong Guang Han - Ong, Guang Han (2016)
Melioidosis is a fatal disease caused by the Gram-negative bacterium, Burkholderia pseudomallei. The routes of infection of melioidosis include ingestion, inhalation and inoculation, with the latter two are believed to be the main routes of infection. The vast clinical manifestations of the infection and the intrinsically antibiotic resistant nature of the bacteria have caused the diagnostic and treatment of the disease difficult. Furthermore, no licensed vaccine for melioidosis has been registered so far. Phage therapy may be the solution for prophylactic prevention and novel antimicrobial agent for melioidosis. Hereby, the potential of phage therapy on B. pseudomallei infection was investigated. Firstly, environmental samples comprising of sewage, soil, fresh and coastal sea water were collected from various locations. These samples were enriched and tested for the presence of B. pseudomallei phages. A total of 43 phages were isolated and their host range was determined against 43 strains of clinical isolates of B. pseudomallei in the lab’s collection. Then, based on their location and host range, five isolates were chosen for propagation and their DNA was extracted for restriction digestion analysis. It was found that they fell under three different restriction profiles. Under transmission election miscroscopy, all three strains were categorised under family Myoviridae. One of the phages, C34 which can constantly propagated to high titre was chosen for time kill curve. The result showed that C34 was able to reduce the bacterial load in liquid culture. Experimental phage therapy was then carried out in cell culture model and mice model. In A549 human lung epithelial cell lines, C34 successfully protected 41.6 ± 6.5% of A549 cells when administered 24 hours prior to B. pseudomallei infection. iv Intraperitoneal injection of phage into intranasal-infected BALB/c mice successfully rescued 33.3% infected mice at the end of the 14 days experiment therapy. It was also shown that phage application was able to reduce the bacterial load in the spleen of the infected mice, and that C34 persisted longer in infected mice as compared to healthy mice injected with C34. In short, C34 can be a potential candidate in phage therapy on B. pseudomallei infections.